Дослідження впливу дефіциту селену на розвиток дифузного зоба в дітей Чернігівської області - Kravchenko, V.I.; Osadtsiv, O.I.; Andrusishina, I.M. (Ендокринологія | Endokrynologia, 2012)
Дослідження впливу дефіциту селену на розвиток дифузного зоба в дітей Чернігівської області